Brainstem Hemorrhage after Evacuation of Chronic Subdural Hematoma: A Case Report and Review of Literature - Gopal, Vinu V.; Mahadevan, K. (Indian Journal of Neurotrauma, 2015)
Brainstem hemorrhage following evacuation of chronic subdural hematoma is extremely rare and its pathogenesis is unclear. In our case report, we present a rare case of brainstem hemorrhage following evacuation chronic subdural hematoma. Our patient was a 50-year-old man, with no comorbidities, presented with dorsal midbrain hemorrhage with ventricular extension and symptomatic progression of contralateral small chronic subdural hematoma following evacuation of chronic subdural hematoma. Contralateral subdural hematoma was evacuated and midbrain hemorrhage was managed conservatively. He was discharged with minimal neurologic deficit. Review of literature and pathogenesis of remote hemorrhage after evacuation of chronic subdural hematoma were discussed.
Keywords: brainstem; hemorrhage; chronic; subdural